Growth and Yield of Mustard as Influenced by Different Combined Doses of Zinc and Boron: Different doses on yield and yield contributing characteristics of mustard (Bangladesh Journal of Agriculture, 2025)
A field experiment was conducted at the research field of BINA substation, Gopalganj from November 2022 to February 2023 to evaluate the effect of different doses of micronutrients (Zn and B) on the growth and yield of mustard. The experiment comprised of eight (8) treatments viz. T0= Control, T1=100% NPKSZnB as Recommended dose of chemical fertilizer (RDCF), T2= 100% NPKS, T3= 100% NPKS+Zn1.5kgha-1+B1.5kgha-1, T4= 100% NPKS+Zn2.0kgha-1+B2.0kgha-1, T5= 100% NPKS+Zn3.0kgha-1+B3.0kgha-1, T6=100% NPKS+Zn2.0kgha-1, T7= 100% NPKS+B2.0kgha-1. The experiment was laid out in a randomized complete block design (RCBD) with three (3) replications. The results revealed that growth and yield were influenced significantly by the rate of 100% NPKS+Zn2.0kgha-1+B2.0kgha-1 application. The highest plant height (103.67 cm), primary branch/plant (6), secondary branch/plant (4.67), lowest days to flowering (35.67), days to maturity (83.00), plant population (728.67), siliqua length (7.30 cm), siliqua/plant (52.67), seeds/siliqua (39.00), 1000 seed weight (4.19 g) and yield (1.99 ton/ha) were obtained from 100% NPKS+Zn2.0kgha-1+B2.0kgha-1 treatment. The result showed that the growth and yield of mustard increased with increasing levels of Zn and B along with 100% NPKS fertilizers application. It may be concluded that the treatment T4= 100% NPKS+Zn2.0kgha-1+B2.0kgha-1 would be suitable for mustard cultivation for getting higher yield and better performance.Bangladesh J. Agri. 2024, 49(2): 101-110